#### Answer

This equation has no solution.

#### Work Step by Step

$\frac{a}{a - 3}$ = $\frac{3}{a - 3}$ - $\frac{3}{2}$
Subtracting $\frac{3}{a - 3}$ from both sides, we get
$\frac{a}{a - 3}$ - $\frac{3}{a - 3}$ = $\frac{3}{a - 3}$ - $\frac{3}{2}$ - $\frac{3}{a - 3}$.
On the left hand side,
the denominators are equal, and thus we can directly subtract the numerators.
Thus,
$\frac{a - 3}{a - 3}$ = -$\frac{3}{2}$ ...(Since $\frac{3}{a - 3}$ - $\frac{3}{a - 3}$ = 0).
$\frac{a - 3}{a - 3}$ = -$\frac{3}{2}$
But,
$\frac{a - 3}{a - 3}$ = 1,
and 1 $\ne$ -$\frac{3}{2}$.
Thus this equation has no solution.